Model Pembelajaran Mata Pelajaran PAI Kelas VIII di SMP Ma’arif Ansoru Al Hasaniyah Rumbia Lampung Tengah - Suryadi, Rahmat; As’ari, Hasyim; Wijaya, Adi (CV. Creative Tugu Pena, 2024)
The learning model is a form of learning that is depicted from beginning to end, which is presented in a unique way by the teacher. Nowadays, many teachers use various teaching strategies to help students succeed in understanding Islamic Religious Education material. However, there are still many models used to teach Islamic Religious Education that tend to be conventional, such as lectures in a straightforward tone that sound monotonous and boring. So it is interesting for researchers to conduct research by raising the title of learning models for Islamic Religious Education subjects in class VIII of Ma'arif Middle School. Ansoru Al Hasaniyah Rumbia. This research was conducted in class VIII of Ma'arif Ansoru Al Hasaniyah Middle School and with the aim of knowing the Islamic Religious Education learning model in class VIII of Ma'arif Ansoru Al Hasaniyah Middle School, Rumbia. The type of research used by the author is qualitative field research. The data collection techniques used in this research are interviews, documentation and observation. The results of this research can be concluded that PAI teachers by implementing this learning model at Ma'arif Ansoru Al Hasaniyah Middle School, Rumbia, Central Lampung, students in class VIII of Ma'arif Ansoru Al Hasaniyah Middle School, Rumbia, Central Lampung become happier and more enthusiastic, critical in thinking, and being a person who cares about others. This is the impact of the learning model that is implemented quite well by PAI teachers, namely in the form of a thematic, cooperative and problem-based learning model, as well as the enthusiasm and activeness of students in the class in participating in the learning process. Keywords: Learning Model, Subjects, Islamic Religious Education